HUBUNGAN ANTARA PENGETAHUAN TENTANG BANTUAN HIDUP DASAR DANMOTIVASI MENOLONG KORBAN KEGAWATDARURATAN PADA MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER - Irfan Helmi Nugroho (FKU 15 UMY 580, 2015)
Background: Basic life support is a procedure to save someone who suffers from medical emergency condition. Required enough motivation to perform emergency aid to the victims. Motivation is important, especially for medical students in performing basic life support in cases of medical emergency that happen everytime. The aim of this study is to determine the relation between knowledge of basic life support andmedical student’s motivation to help victims of emergency by using questionnaires that have been validated. Methods: This studyis an analytical correlation non-experimental design with cross sectional approach. The study included 63 medical students from Muhammadiyah University of Yogyakarta. Data analysis was performed using Spearman'stest. Results: Knowledge of basic life support are 43 students (75.4%) have a high level of knowledge, medium 9 student (15.8%) and low 5 student (8.8%). The level of motivation to help victims of emergency 46 people (80.7%), while 10 students (17.5%) get medium level and low level is one student (1.8%). Statistical analysis showed that the value of p=0.000 with Spearman correlation value of 0.603 which indicates this study are meaningful and have a positive correlation values with the strong correlation. Conclusion: There is a strong relation between knowledge of basic life support and motivation to help victims of emergencies in medical students from Muhammadiyah University of Yogyakarta